2010
DOI: 10.1016/j.amjmed.2010.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Outcomes in Very Old Hypertensive Coronary Artery Disease Patients: An INVEST Substudy

Abstract: BACKGROUND-Our understanding of the growing population of very old patients (aged ≥80 years) with coronary artery disease and hypertension is limited, particularly the relationship between blood pressure and adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 21 publications
2
82
0
6
Order By: Relevance
“…BP indicates blood pressure; DBP, diastolic blood pressure; and SBP, systolic blood pressure. Reprinted from Denardo et al 13 among those with prior revascularization, suggesting more severe vascular disease, and again the J-curve between BP and mortality, MI, or stroke was observed even with propensity score adjustment.…”
Section: Aronow Et Al Hypertension In the Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…BP indicates blood pressure; DBP, diastolic blood pressure; and SBP, systolic blood pressure. Reprinted from Denardo et al 13 among those with prior revascularization, suggesting more severe vascular disease, and again the J-curve between BP and mortality, MI, or stroke was observed even with propensity score adjustment.…”
Section: Aronow Et Al Hypertension In the Elderlymentioning
confidence: 99%
“…584 In INVEST, the nadir BP for risk was 135/75 mm Hg among 6126 patients 70 to 80 years of age, and 140/70 mm Hg for 2180 patients Ն80 years of age. 13 Beta blockers with intrinsic sympathomimetic activity must not be used after MI. The hydrophilic beta blocker atenolol may not be as efficacious as propranolol, timolol, metoprolol, or carvedilol in treating hypertension, 617,618 but in most of the patients in these studies (eg, LIFE), it was used only once daily.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Very few studies have addressed this question, but those that have addressed it have produced reasonably reassuring results. An INVEST substudy 158 showed a J-shaped relationship between DBP and the primary outcome (all-cause death, nonfatal MI, or nonfatal stroke) but with a nadir of 75 mm Hg, except for the very old, for whom it was even lower at 70 mm Hg. In HYVET, 15 patients >80 years of age with a mean BP of 173.0/90.8 mm Hg were randomized to receive treatment with indapamide, with perindopril added if necessary, versus placebo.…”
Section: The Elderlymentioning
confidence: 99%
“…Conversely, studies of people in advanced age have shown a non-linear relationship between BP and all-cause mortality [31]. The lowest hazard ratio for adverse outcomes was at SBP 140 mmHg [32], suggesting the optimal BP for these people may be higher than currently recommended.…”
Section: Discussionmentioning
confidence: 97%